Impact of cancer on cryopreserved sperm quality and fertility: A cohort study - David Pening; Marnie Constant; Manon Bruynbroeck; Anne Delbaere; I. Demeestere (Health Science Reports, 2022)
Abstract Background Sperm quality at cancer diagnosis is often compromised by the disease and any given gonadotoxic treatment will further diminish fertility. Objectives Here, we aim to analyze the cryopreserved sperm quality according to the cancer types as well as the fertility outcomes. Methods Our study included all cancer patients who cryopreserved sperm over 20 years at Erasme Hospital Brussels (from 1999 to 2019). First sperm samples from 111 hematologic, 104 testicular, 19 prostate, 28 gastrointestinal, and 16 neurological cancer patients were compared. Results Oligozoo‐asthenozoospermia was observed in 30% of the samples, including 19.33% with severe oligozoospermia (<5 million/ml). Our results showed a significant reduction in sperm concentration among testicular cancer (p < 0.01). No significant differences in progressive motility, sperm volume, and number of frozen straws were observed. Significant correlations were found between sperm concentration and cancer type (p <0.01) as well as patients' age (p <0.01). Twenty‐eight cancer survivors returned for using their cryopreserved sperm (9.33%), fertilization rate was 60.5% and implantation rate was 29.6%. There was no correlation between sperm concentration and fertility outcomes. Conclusion Our results confirm the negative impact of cancer on sperm quality without affecting assisted reproductive technology (ART) success rate, which is utterly important as a male reproductive health perspective. All cancer patients should be counselled and offered fertility preservation options as a gold standard.